Nonspecific Cytotoxic Cell Receptor Protein-1: A Novel (Predicted) Type III Membrane Receptor on the Teleost Equivalent of Natural Killer Cells Recognizes Conventional Antigen - Evans, Donald L.; Leary, John H.; Jaso-Friedmann, Liliana (Cellular immunology, 1998)
The phylogenetic model for “conventional” antigen recognition by NK cells may be a protein (NCCRP-1) recently identified from catfish nonspecific cytotoxic cells (NCC). NCCRP-1 may be a Type III membrane protein. The antigen binding domain was identified by competition experiments using synthetic peptides. Within this domain, a 38-mer peptide (aa 104–140) inhibited NCC killing of IM-9, HL-60, NC-37, U937, and MOLT-4 target cells. Biotinylated 38-mer also bound to IM-9 target cells. A mab which inhibited conjugate formation between NCC and target cells also bound to the 38-mer. Nonbiotinylated 38-mer inhibited mab 5C6 binding to immobilized homologous biotinylated peptide in cold competition ELISA experiments. Peptide 104–140 was truncated into two peptides. Amino acid 104–119 bound to (68%) and inhibited lyis of IM-9 target cells, whereas aa 120–140 had no activity. A predicted structure–function algorithm suggested an N-terminal domain containing BOX-1 motifs for cytokine activation; a C-terminal domain containing abundant phosphorylation sites (i.e., Y, S, and T amino acids); and an extracellular antigen binding domain..